Are the correlates of sport participation similar to those of screen time? - Mark S. Allen; Stewart A. Vella (Preventive Medicine Reports, 2015)
Objective: To explore longitudinal and cross-sectional correlates of sport participation and screen time in a nationally representative sample of Australian children. Methods: The sample included 3956 child participants taken from the Longitudinal Study of Australian Children. Data were collected in 2004 (age range = 4–5 years) and 2012 (age range = 12–13 years) and included parental estimates of sport participation and total screen time (electronic gaming and television viewing) in addition to demographic, socioeconomic and environmental factors. Results: Sport participation and total screen time were inversely correlated (r = −.10). Child demographics (sex, pubertal status, general health, and body mass index [BMI]), socioeconomic (neighborhood socioeconomic position, household income, parental education, and parental BMI) and environmental (neighborhood belonging, neighborhood safety, and neighborhood facilities) factors were related to both outcomes — in most cases a positive [negative] correlation with sport participation yielded a corresponding negative [positive] correlation with total screen time. Conclusion: Our findings show that demographic, socioeconomic and environmental factors measured at age 4 predict sport participation and screen time at age 12, and that the correlates of childhood sport participation and childhood sedentary behavior may be more similar than previously estimated.